EFFECT OF CREDIT REFERENCE BUREAU SERVICES ON NON-PERFORMING LOAN PORTFOLIOS IN KENYA. “A CASE STUDY OF DEPOSIT TAKING MICROFINANCE INSTITUTIONS” - OMARE, HILLARY MARANGA (My University, 2016)
The research project sought to examine the effect of listing with Credit Reference Bureau service on non-performing loans of deposit taking microfinance institutions in Kenya. The specific objectives were to assess how loan recoveries as a result of listing with credit reference bureau affects non-performing loans by deposit taking microfinance institutions in Kenya, to assess how write offs as a result of listing with credit reference bureau affect nonperforming loans by deposit taking microfinance in Kenya, to examine how loan quality as a result of listing with credit reference bureau affect non-performing loan in deposit taking microfinance in Kenya and what effect does listing with credit reference bureau has on nonperforming loans levels in Deposit Taking Microfinance in Kenya. This research study adopted a descriptive survey approach on effect of listing with Credit Reference Bureau Service on non-performing loans of deposit taking microfinance institutions in Kenya. Further, this study targeted all registered deposit taking microfinance institutions by the Central Bank of Kenya (CBK). Target population was 12 registered Deposit taking microfinance institutions that have listed with Credit Reference Bureaus in Kenya. This study used primary data that was collected by use of a questionnaire. The data was analyzed by use of Descriptive and inferential statistics to measure interrelationships between the variables. Tables were used to display the information to improve presentation of the analyzed results for ease of interpretation. Regression analysis was used to test the relationship between dependent and independent variable. In light of the research findings, the regression model could only explain 52% in variance of non-performing loans. The study results revealed that there was a statistically significant relationship between loan recoveries and nonperformance of loans (p=0.000); there was a statistically significant relationship between write offs and non-performance of loans (p=0.000) and that there was a statistically significant relationship between quality loan portfolio and non-performance of loans (p=0.000). Hence, credit information sharing and level of nonperforming loans are indeed related meaning there is a direct relationship between the number of credit checks done by the CRBs and the level of NPLs. It is thus recommended that a study be carried out consisting of other factors which were not part of the model to predict non-performing loans. The findings of this study would be useful to the D.T.M’s Banks in Kenya, as it will help the banks in formulating effective policies related to reducing non-performing loans in Kenya. In addition, the findings of the study would also be useful to the microfinance institutions as it would be insightful on how this institutions can increase and control credit distribution to their clients.
FULL TEXT
Keywords: Credit Reference Bureau, Deposit Taking Micro-Finance, Writing off, and Recoveries.